2018
DOI: 10.1155/2018/1751857
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Optical Coherence Tomography Angiography and Laser Speckle Flowgraphy for the Diagnosis of Normal-Tension Glaucoma

Abstract: Purpose To compare optical coherence tomography angiography (OCT-A) and laser speckle flowgraphy (LSFG) for the diagnosis of normal-tension glaucoma (NTG). Methods Twenty-eight eyes of 28 patients with NTG and 25 eyes of 25 normal subjects matched for age, refractive errors, systemic blood pressure, and central corneal thickness were evaluated. OCT-A was used to measure whole image vessel density, inside disc vessel density, and peripapillary vessel density; using LSFG, mean blur rate (MBR) inside the whole op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…A consequence of the nonmonotonic relation between severity and blood flow is that the parameter MBR ave is unlikely to be useful for the diagnostic detection of disease since a value within normal limits would reappear after considerable loss of axons. This may explain why vessel density measured using OCTA has been reported as having better discriminatory power between eyes with glaucoma versus controls than do LSFG parameters 58. Other LSFG parameters may prove more useful for discrimination than MBR ave .…”
Section: Discussionmentioning
confidence: 99%
“…A consequence of the nonmonotonic relation between severity and blood flow is that the parameter MBR ave is unlikely to be useful for the diagnostic detection of disease since a value within normal limits would reappear after considerable loss of axons. This may explain why vessel density measured using OCTA has been reported as having better discriminatory power between eyes with glaucoma versus controls than do LSFG parameters 58. Other LSFG parameters may prove more useful for discrimination than MBR ave .…”
Section: Discussionmentioning
confidence: 99%
“…Within the perimetrically undamaged area, RNFL was significantly lower in the superior nasal and upper nasal sectors (P=0.02) but VD showed no changes 11 . For NTG, a change in vascular density in the peripapillary region was registered [12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a comparison of MBR obtained by LSFG with the peripapillary relative intensity (PRI) acquired by OCTA, superficial-choroidal PRI was found significantly correlated with MBR in the ONH tissue area 21. Another study found OCTA vessel density had a higher glaucoma diagnostic ability compared to LSFG parameters in patients with normal tension glaucoma (NTG) 22. Thus, LSFG and OCTA are both useful tools for managing glaucoma, and it is considered to be meaningful to investigate the relationship between the two more deeply.…”
Section: Introductionmentioning
confidence: 99%